Combinatorial Properties of Strength Groups in Round Robin Tournaments - Dirk Briskorn (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2006)
A single round robin tournament (RRT) consists of a set T of n teams (n even) and a set P of n - 1 periods. The teams have to be scheduled such that each team plays exactly once against each other team and such that each team plays exactly once per period. In order to establish fairness among teams we consider a partition of teams into strength groups. Then, the goal is to avoid a team playing against extremely weak or extremely strong teams in consecutive periods. We propose two concepts ensuring different degrees of fairness. One question arising here is whether a single RRT exists for a given number of teams n and a given partition of the set of teams into strength groups or not. In this paper we examine this question. Furthermore, we analyse the computational complexity of cost minimization problems in the presense of strength group requirements.
Keywords: 650; Round robin tournaments; fairness; partition of teams; strength groups